PENGARUH FED RATE, HARGA MINYAK DUNIA, BI RATE, INFLASI DAN KURS RUPIAH TERHADAP INDEKS SAHAM SYARIAH INDONESIA (ISSI) PERIODE TAHUN 2011-2017 - Citra Puspa Mawarni; Anny Widiasmara (Universitas PGRI Madiun, 2018)
The purpose of this study is to analyze the effect of FED Rate, World Oil Price, BI Rate, Inflation and Rupiah Rate to Indonesia Sharia Stock Index (ISSI) Period 2011-2017. The population of this study are Indonesian Sharia Stock Index, FED Rate, World Oil Price, BI Rate, Inflation and Rupiah Exchange Rate in 2011-2017. Determination of the sample using the census method by taking the entire population. This study uses secondary data, time series with the amount of data as much as 72 periods. Data analysis in this study used multiple linear regression analysis, t test statistic, F statistical test, and coefficient of determination test (R2) with the help of computerprogram SPSS version 17. The result of this analysis shows that the variable of the Rupiah Exchange Rate has a significant negative effect to the Indonesian Sharia Stock Index. However, the variable FED Rate, World Oil Price, BI Rate, and Inflation did not have a significant effect on Indonesian Sharia Stock Index.Keyword : Indonesia Sharia Stock Index, FED Rate, World Oil Price, BI Rate, Inflation, Rupiah Exchange Rate